Computational statistics and data analysis (Elsevier, 2018)
Computational Statistics & Data Analysis, is an international journal dedicated to the dissemination of methodological research and applications in the areas of computational statistics and data analysis. Computational Statistics & Data Analysis, es una revista internacional dedicada a la divulgación de investigaciones y aplicaciones metodológicas en las áreas de estadística computacional y análisis de datos.